Duodenum Histomorphology of Bacillus subtilis and Bacillus coagulan Isolate in Laying Hen Strain Isa Brown - Muzhaffar, Adam Maulana; Hamid, Iwan Sahrial; Effendi, Mustofa Helmi; Wibawati, Prima Ayu; Sukmanadi, Mohammad; Solfaine, Rondius (Journal of Basic Medical Veterinary, 2023)
Probiotics are live microbes that are used as supplementary feed that work to increase the good bacteria that live in the digestive tract by suppressing pathogenic microorganisms in the intestine so that good bacteria can grow can optimize the feed absorption process. This study aims to determine the effect of adding probiotics as feed additive Against the height and width of the duodenal villi of the laying chicken in early production. Probiotics can nourish the digestive tract and increase nutrient digestibility so that nutrient intake is met for livestock. Bacillus subtilis and Bacillus coagulans as a prophylaxis against bacterial diseases by balancing intestinal microbes, increasing digestibility, and secreting protease, lipase, and amylase enzymes. The purpose of this study was to determine the effect of probiotics Bacillus subtilis and Bacillus coagulans on duodenal histomorphology. Twenty-four layers were randomly divided into 4 groups. The control group was not given probiotics, groups P1, P2, and P3 were given probiotics of 2 ml, 4 ml, and 6 ml. Probiotics were given for 14 days. One-way ANOVA showed a significant difference in each group (P<0.05) and continued with the DUNCAN test. The average length and width of the duodenal villi in each treatment showed that the control group was significantly different from the P1, P2, and P3 groups. The P3 group had the highest average length of duodenal villi. The increase in villi height and villi width is due to the increase in short-chain fatty acids induced by probiotics. An increase in the height and width of villi indicates the absorption capacity of the small intestine, the work of digestive enzymes on the intestinal mucosa is more maximal in the intestine with a wider morphological size, so that absorption and growth are better. The conclusion from the research that has been done is that the use of Bacillus subtilis and Bacillus coagulans as probiotics has an effect on the layer duodenal villi which is characterized by an increase in the average length of the duodenal villi according to the increase in the probiotic dose.